Complement activation in pemphigus vulgaris blister fluid - Jordon, R. E. (1973)
Total haemolytic complement was reduced in blister fluids of four pemphigus vulgaris patients when compared to serum complement levels and other serum and blister fluid proteins. Complement levels in most control blister fluids, on the other hand, more closely approached their corresponding serum levels. Haemolytic C1, C4, C2, C3 and C5, measured in two pemphigus sera and blister fluids, were not measurable in one blister fluid and were extremely low in the second patient. C3 proactivator (C3PA) was absent from both of these blister fluids. Three of the blister fluids exhibited anti-complementary activity when tested with normal human serum. By adding one blister fluid to normal human serum, inhibition of haemolytic C1, C2, C3 and C5 with conversion of C3 and C3PA occurred. Activation of complement locally in pemphigus blister fluids would suggest a pathogenetic role for complement in this disease.